Gender Equality of Salafi Family in Dieng - Mazid, Sukron - (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
This study aims to identify gender equality of Salafi families in Dieng’s social life that urge the existence of men and women’s roles in the Salafi families. This study applied descriptive qualitative method using case study approach in Kepakisan Village, Batur District, Banjarnegara Regency. The results indicate that the Salafi family's social life includes the social environment, education, and occupation. The Salafi familes are fairly treated without being discriminated such as in social activities and community works. All Salafi children are given equal access and opportunities in education, in which the main focus is religious education. In terms of occupation, Salafi men and women are also given equal access and benefits especially in agricultural sector where husband and wife can work together and help each other.